Epigenetic Modifications in Cellular Senescence: Mechanisms, Implications, and Therapeutic Potential - Mohammed Adam, Ahmed; Imran Khan, Mohammad; Alzahrani, Faisal (Journal of King Abdulaziz University: Science, 2024)
Stressors, has attracted attention in the biological and medical sciences. Epigenetic modifications, which impact gene expression patterns and ultimately dictate the fate of cells, play a crucial role in managing cellular senescence. DNA methylation is a crucial epigenetic process implicated in cellular senescence. Research has demonstrated that changes in gene expression profiles result from global hypomethylation and localized hypermethylation of genes during senescence. Cellular senescence is also significantly influenced by histone alterations. Histone acetylation or methylation can change the chromatin structure, which can impact transcription factors’ ability to bind to gene promoters. Consequently, this may have an impact on the expression of genes linked to senescence processes. Furthermore, due to their capacity to post-transcriptionally control gene expression, non-coding RNAs like microRNAs have become significant regulators of cellular senescence. Dysregulation of microRNAs has been linked to the induction or inhibition of senescence in different cell types. In this comprehensive review, we discuss the epigenetic modifications that occur during cellular senescence and explore their potential as therapeutic targets to regulate the senescent phenotype, a crucial step in addressing age-related diseases.